Solar erythemal UV radiation climatology over Slovakia - PRIBULLOVÁ, Anna; CHMELÍK, Miroslav (Contributions to Geophysics and Geodesy, 2021)
Maps of the solar erythemal ultraviolet (UV) radiation daily doses were created for every month with horizontal resolution of 500 m at geographical domain 47.15N – 49.86N x 16.94E – 22.81E covering the territory of Slovakia. Cloud modification factor for the UV radiation (cmfUV) was modelled utilizing a relation between the cmf of the total and UV radiation. Measurements of total ozone performed by the Brewer spectrophotometer at Poprad – Gánovce (inside the investigated domain) were considered representative for selected geographical area. Information on snow cover presence was the only meteorological parameter used in the model. Verification of the model was performed at 5 observatories equipped with broadband solar UV radiometers. The maps of the cmf factor of the UV radiation were created utilizing measurements of total radiation performed at 9 observatories during 1995 – 2004 period and the model of cmf dependence on altitude. Maps of clear-sky UV radiation daily dose and UV radiation daily dose affected by average cloudiness were constructed for mean monthly total ozone, their upper and lower monthly limits, for two probability levels of snow cover occurrence as a criterion for the snow effect incorporation in the model and for 1 day representing typical values of every month. The maps of the erythemal UV radiation daily doses were created for average and limit conditions of factors affecting the erythemal UV radiation. The map-set can be considered as an atlas of the solar erythemal UV radiation over Slovakia.